Patterns and predictors of recurrence after laparoscopic resection of rectal cancer - Yang, Hong; Chen, Lei; Wu, Xiuxiu; Zhang, Chenghai; Yao, Zhendan; Xing, Jiadi; Cui, Ming; Jiang, Beihai; Su, Xiangqian (Frontiers in Oncology, 2022)
Purpose: This study was designed to evaluate the patterns and predictors of recurrence in patients who underwent laparoscopic resection of rectal cancer. Methods: Patients with rectal cancer receiving laparoscopic resection between April 2009 and March 2016 were retrospectively analyzed. The association of recurrence with clinicopathological characteristics was evaluated using multivariate analyses. Results: A total of 405 consecutive patients were included in our study. Within a median follow-up time of 62 months, 77 patients (19.0 %) experienced disease recurrence: 10 (2.5 %) had locoregional recurrence (LR), 61 (15.1 %) had distant metastasis (DM), and 6 (1.5 %) developed LR and DM synchronously. The lung was the most common site of metastasis. Multivariate analyses indicated that involved circumferential resection margin (CRM) was the only independent predictor for LR (OR=13.708, 95% CI 3.478-54.026, P＜0.001), whereas elevated baseline level of CA19-9 (OR=3.299, 95% CI 1.461-7.449, P=0.032), advanced pN stage (OR=2.292, 95% CI 1.177-4.462, P=0.015) and harvested lymph nodes less than 12 (OR=2.418, 95% CI 1.245-4.695, P=0.009) were independently associated with DM. Patients receiving salvage surgery showed superior 3-year survival compared with palliative treatment after relapse (90.9 % vs. 20.5 %; P=0.017). The estimated 5-year DFS and CSS for the entire cohort was 80.2 % and 83.1 %, respectively. Conclusions: DM was more common than LR after laparoscopic resection of rectal cancer, and there were several clinicopathological factors related to LR and DM. Involved CRM and suboptimal lymph node yield were adverse surgery-related factors of tumor recurrence, which should be paid more attention to during the operation.